Mythical trickster figures : contours, contexts, and criticisms - Hynes, William J.; Doty, William G., 1939- (University of Alabama Press, 1993)
Mythical Trickster Figures, is the first substantial collection of essays about the trickster to appear since Radin's 1955 The Trickster. Contributions by leading scholars treat a wide range of manifestations of this mischievous character, ranging from the Coyote of the American Southwest to such African figures as Eshu-Elegba and Ananse, the Japanese Susa-no-o, the Greek Hermes, Christian adaptations of Saint Peter, and examples found in contemporary American fiction and drama. The many humorous trickster stories included are fascinating in themselves, but Hynes and Doty also highlight the wi.